Dietary assessment of human exposure to PBDEs in South Korea - Na, Sumin; Kim, Meehye; Paek, Ockjin; Kim, Yunje (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
This study was conducted to measure the concentration of PBDEs in various food stuffs from Korea and to estimate levels of PBDE intake from food for the Korean population according to geographical location and age. 20 types of food samples were collected from four heavily populated cities (Seoul, Gwangju, Daejeon, Pusan) and one rural city (Gangneung) and were analyzed for 19 polybrominated diphenyl ether congeners (BDE 15, 17, 28, 33, 47, 49, 66, 71, 85, 99, 100, 119, 126, 138, 153, 154, 183, and 209). No significant differences in total PBDE levels in foods were found among four large cities (Gwangju; 10.91 ng g(-1) wet weight (ww), Seoul; 7.66 ng g(-1) ww, Daejeon; 6.91 ng g(-1) ww, Pusan; 6.87 ng g(-1) ww) and one rural city (Gangneung; 8.72 ng g(-1) ww). Daily dietary intake of PBDEs does not appear to be related to the extent of urbanization. Total dietary intake of PBDE for the average general population was 72.30 ng d(-1) (not detected (ND) = 0) which was similar to other countries. In all food groups, the largest contribution to PBDE intake was from fish and shellfish (48.96 ng d(-1)). Total PBDE consumed per kilogram of body weight was estimated to range from 2.70 ng kg(-1) d(-1) for infants 1 through 2 years of age to 0.85 ng kg(-1) d for 65 years and older and was highest in young children and decreased with increasing age. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: POLYBROMINATED DIPHENYL ETHERS; BROMINATED FLAME RETARDANTS; POLYCHLORINATED-BIPHENYLS; UNITED-STATES; TREND; FOOD